ХХ ӘСИРДИҢ 60-80 -ЖЫЛЛАРЫНДАҒЫ ҚАРАҚАЛПАҚ БАЛАЛАР ФОЛЬКЛОРЫНЫҢ ИЗЕРТЛЕНИЎ ТАРИЙХЫ - Календерова, А.М. (ILIM hám JÁMIYET, 2021)
The article deals with the history of the study of Karakalpak children’s folklore in 1960-1980. The author of the article, having studied scientific publications, comes to the conclusion that children’s folklore in those years was not considered as a separate science, but some issues were considered in small genres of Karakalpak folklore. The names of the authors and the title of the article, the content and essence of the research are indicated.